Cells mediating graft rejection in the mouse. I. Lyt-1 cells mediate skin graft rejection (The Rockefeller University Press, 1981)
The Ly phenotype of cells mediating skin graft rejection was determined using monoclonal anti-Lyt-1.1 and Lyt-2.1 antibodies in CBA mice that received CBA lymphoid cells from mice sensitized to C57BL/6; i.e., alloantigenic differences arising from the H-2 and non-H-2 loci. It was clear that graft rejection was due wholly to the presence of Lyt-1 cells in the inoculum and that Lyt-123 or Lyt-23 cells had no effect. Furthermore, no synergism was noted between Lyt-1 and Lyt-2 cells. In this model, both the cytotoxic T cell and cytotoxic lymphocyte precursors were shown to be Lyt-123 and these could be depleted from sensitized Lyt-1 populations that mediated graft rejection. Thus cytotoxic T cells are not responsible for skin graft rejection, but rather, this is mediated by an Lyt-1 cell. Whether this T cell is distinct from other Lyt-1 cells (T helper, T cells mediating delayed hypersensitivity) is not clear at present, but other evidence, and traditional concepts, link graft rejection and delayed type hypersensitivity as being different manifestations of the same mechanism.